Penggunaan Metode Dialog (Muhawaroh) dalam Keterampilan Berbicara Bahasa Arab Kelas VII di MTs Daarul Ma’arif Purwakarta - Julianti Julianti; Susilawati Susilawati; Dede Rizal Munir (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study discusses several things regarding: 1) the use of the dialogue method (muhawaroh) in speaking Arabic at MTs Daarul Ma'arif, 2) the advantages and disadvantages of using the dialogue method (muhawaroh) in speaking Arabic at MTs Daarul Ma'arif. This study uses descriptive qualitative research with data collection methods by conducting interviews, observations, and documentation. After the data is collected, then data analysis is carried out using the theory of John Creswell. The results of the research obtained are learning using the muhawaroh dialogue method is more effective than other methods. Because by using this method, students look more active and interactive and also enthusiastic in learning what is conveyed. Teachers of Arabic subjects have been trying to improve the mastery of dialogue in Arabic in learning activities, the teacher always repeats the material that has been taught. This method is carried out by the teacher having a dialogue with his students on the hiwar material so that the overall mastery of Arabic dialogue in the learning process can be achieved so that students are skilled in speaking Arabic. The advantage of this method is to increase students' enthusiasm and interest in learning, with this method students can practice the conversation ahead and students don't feel nervous anymore. The drawback of this metkhod is, for some students the Arabic dialogue seems scary, for fear of pronouncing it wrong.